I'm pretty sure it's
3.648 x 10(exponent 3)
Answer:
Lots of "ifs" here.
A=bh/2 is the formula for the area of a triangle.
A=bh is the formula for the area of a rectangle or a parallelogram.
If the 6 & 4 area the base & height of a rectangle, then (6)(4) = 24 in^2
If the 6 & 10 are the base and height of a triangle, then 1/2(6)(10) = 30 in^2
Step-by-step explanation:
Perpendicular line always have slopes that are negative reciprocals of one another. Mathematically,
m1*m2=-1
So to be perpendicular to the line given, let's rearrange it to the point slope form of a line...
3y=6x ?3 (not sure what you wanted to type there)
anyway isolating y by dividing both side by three will leave 2x where 2 is the slope.
So for the other line to be perpendicular, m*2=-1, m=-1/2, now we have:
y=-x/2 +b, we can now you the point given to solve for b
4=-2/2 +b
4=-1+b
b=5 so
y=-x/2 +5 or more neatly
y=(10-x)/2
Step-by-step explanation:
You can write an equation of a line conveniently by point-slope form. It's in the form of
where
is the coordinates of a point that's on the line and
is the slope of the line.
Now choose a point (It doesn't really matter which one) and plug that in the equation. I'll choose
where
and ![b = -3](https://tex.z-dn.net/?f=b%20%3D%20-3)
![y -a = m(x -b) \\ y -7 = m(x -(-3)) \\ y -7 = m(x +3)](https://tex.z-dn.net/?f=y%20-a%20%3D%20m%28x%20-b%29%20%5C%5C%20y%20-7%20%3D%20m%28x%20-%28-3%29%29%20%5C%5C%20y%20-7%20%3D%20m%28x%20%2B3%29)
The next thing we have to do now is finding the slope,
, where it's equal to
. I'll make
point 1 and
point 2.
![m = \frac{3 - 7}{3 -(-3)} \\ m = \frac{3 - 7}{3 +3} \\ m = \frac{-4}{6} \\ m = -\frac{2}{3}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B3%20-%207%7D%7B3%20-%28-3%29%7D%20%5C%5C%20m%20%3D%20%5Cfrac%7B3%20-%207%7D%7B3%20%2B3%7D%20%5C%5C%20m%20%3D%20%5Cfrac%7B-4%7D%7B6%7D%20%5C%5C%20m%20%3D%20-%5Cfrac%7B2%7D%7B3%7D)
Now let's plug that to our equation.
![y -7 = m(x +3) \\ y -7 = -\frac{2}{3}(x +3)](https://tex.z-dn.net/?f=y%20-7%20%3D%20m%28x%20%2B3%29%20%5C%5C%20y%20-7%20%3D%20-%5Cfrac%7B2%7D%7B3%7D%28x%20%2B3%29)
Now we have the equation but out of all the choices it seemed that all of them are in slope-intercept form all you have to do now is make our equation rewrite it in slope-intercept form.
![y -7 = -\frac{2}{3}(x +3)\\ y -7 = -\frac{2}{3}x -\frac{2}{3}(3) \\ y - 7 = -\frac{2}{3}x -2\\ y = -\frac{2}{3}x +5](https://tex.z-dn.net/?f=y%20-7%20%3D%20-%5Cfrac%7B2%7D%7B3%7D%28x%20%2B3%29%5C%5C%20y%20-7%20%3D%20-%5Cfrac%7B2%7D%7B3%7Dx%20-%5Cfrac%7B2%7D%7B3%7D%283%29%20%5C%5C%20y%20-%207%20%3D%20-%5Cfrac%7B2%7D%7B3%7Dx%20-2%5C%5C%20y%20%3D%20-%5Cfrac%7B2%7D%7B3%7Dx%20%2B5)
<h3>Answer:</h3>
is your equation.